Medical Devices Made of Substances: A New Challenge - Leone, Maria Grazia (Frontiers in Drug Safety and Regulation, 2022)
Regulation (EU) 2017/745 provides for new provisions for medical devices made of substances as well as specific classification rules and requirements, definitively legitimizing their qualification as MDs. The demarcation line between medical devices composed of substances and medicinal products is not always easy to define. The recent publication by the European Commission of the guidance on borderline between medical devices and medicinal products under the Regulation (EU) 2017/745 on medical devices, MDCG 2022-5, addresses some important issues in this topic. This article will discuss some controversial aspects in this field in order to clarify the product qualification process.The topics covered in this article will have great relevance for the future of substance-based MDs.